PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN REAL ESTATE AND PROPERTY - Fatmawati, Hanna Rossita Septiwulan; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTInvestment decision is a problem which is commonly encountered by investors. In conducting investment, investors should know in advance a bout the state of the performance of the company and the relevant information about the financial condition of a company. The financial performance reflects one of the performances of the company. The financial performance of the company can be measured by using the financial statement of the company. Good financial performance will give an impact to the stock prices. The samples in this research have been obtained by using purposive sampling on real estate and property companies which are listed in Indonesia Stock Exchange in 2011- 2014 periods and based on the predetermined criteria 29 real estate and property companies have been selected as samples. The analysis method has been done by using multiple linear regressions analysis and the SPSS software tool. The result of the research shows that the return on asset which gives significant and positive influence to the stock price. Net profit margin which does not give any significant and negative influence to the stock prices. Debt to asset ratio does not give any significant and positive influence to the stock prices. Price earnings ratio which does not give any significant and positive influence to the prices. And simultaneously return on assets, net prof it margin, debt to asset ratio and price earnings ratio give significant influence to the stock prices.Keywords: Return on Asset, Net Profit Margin, Debt to Asset Ratio, Price Earnings Ratio, Stock Price